Biology, genetics, and ecology of the cosmopolitan ectomycorrhizal ascomycete Cenococcum geophilum - Wang, Huayong; Kohler, Annegret; Martin, Francis M. (Frontiers in Microbiology, 2025)
The ascomycete Cenococcum geophilum is a cosmopolitan and ecologically significant ectomycorrhizal (ECM) fungus that forms symbiotic associations with diverse host plants worldwide. As the only known ECM species within the large class Dothideomycetes, C. geophilum exhibits several characteristics that distinguish it from other ECM fungi. This fungus significantly contributes to ecosystem stability and development as an early colonizer of primary forest succession. The capacity of this symbiont to rapidly colonize disturbed or newly formed environments promotes the development of conditions that support the growth of other plant species, thus playing a crucial role in the ecological progression and restoration of ecosystems. Several C. geophilum isolates are known to enhance the drought resistance of host plants, a trait that is becoming increasingly important in the context of climate change and frequent drought events. In this review, we examined genetic studies that have assessed the phylogenetic structure of C. geophilum populations and identified the genes associated with adaptation to environmental stress and symbiosis. The high genetic diversity of C. geophilum is particularly noteworthy, considering its putative asexual reproductive mode. Population genomic analyses have suggested that C. geophilum is not a single species but rather a species complex comprising multiple cryptic lineages. This genetic variability may contribute to its adaptability and extensive distribution across habitats from circumpolar to tropical biomes. These lineages exhibit potential host preferences, suggesting a degree of specialization within the complex. The nuclear genome of C. geophilum has been sequenced, providing valuable insights into the symbiont genetic traits. Notably, this genome encodes a large set of repeated sequences and effector-like small secreted proteins. Transcriptomics has been used to identify candidate genes related to symbiosis and adaptation to environmental stress. Additionally, we briefly discuss how C. geophilum offers potential for sustainable forestry practices by improving resilience to stress.